Sociocultural Pragmatic Differences of Complaining in English Shushanik Paronyan - Paronyan, Shushanik (Bulletin of Yerevan University B: Philology, 2026)
Being a sociocultural phenomenon, language enables people to communicate to other members of the society as well as to one’s inner self. By analyzing verbal behavior, or the communicative aspect of language, Pragmatics highlighted the necessity to reckon certain extralinguistic factors when creating meaning, such as the speakers’ intents, communicative goals, personal attitudes and feeling, as well as their sociocultural characteristics. The aim of this paper is to investigate the communicative-pragmatic peculiarities of complaint in English. Complaint is placed among Expressives, a class of speech acts that state what the speaker feels. On the illocutionary level, complaints express negative emotional message, the complainers’ disapproval about a certain situation or dissatisfaction with some state of affairs. The research of the practical material carried out in this paper shows that complaints, like other speech acts, can be phrased with the help of direct and indirect speech acts. Having an adversative illocutionary content, complaint depends heavily on the principles of politeness that govern the process of communication. The research attempts to illustrate how certain social factors affect the language choice by the speakers in the process of complaining.
Keywords: Pragmatics; Speech Act Theory; politeness principles; complaining; direct/indirect speech acts